2016
DOI: 10.1016/j.jad.2016.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase inhibitors and memantine in bipolar disorder: A systematic review and best evidence synthesis of the efficacy and safety for multiple disease dimensions

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Likewise, previous preclinical reported data demonstrated that the association of MEM with antidepressant drugs, such as fluoxetine and venlafaxine enhances the antidepressant effect of classical therapies. MEM associated with galantamine was investigated in the treatment of cognitive deficits in with schizophrenia [ 120, 121 ]. Others clinical trial evaluated, a part of MEM, additional non-pharmacological strategies for example the Environmental Ecological Therapy in AD [ 122, 123 ].…”
Section: Clinical Trials With Memantinementioning
confidence: 99%
“…Likewise, previous preclinical reported data demonstrated that the association of MEM with antidepressant drugs, such as fluoxetine and venlafaxine enhances the antidepressant effect of classical therapies. MEM associated with galantamine was investigated in the treatment of cognitive deficits in with schizophrenia [ 120, 121 ]. Others clinical trial evaluated, a part of MEM, additional non-pharmacological strategies for example the Environmental Ecological Therapy in AD [ 122, 123 ].…”
Section: Clinical Trials With Memantinementioning
confidence: 99%
“…The analysis of the data concerning the usefulness of the cholinesterase inhibitors galantamine and donepezil as well as the glutamate receptor antagonist memantine was negative (Veronese et al, 2016). …”
Section: Efficacy Datamentioning
confidence: 99%
“…Finally, a meta-analysis reported that the probability of receiving placebo, baseline illness severity, and trial duration correlate with placebo response rates and/or clinical trial outcome in RCTs of pharmacotherapy for bipolar depression (Nierenberg et al, 2015), while another one was negative concerning the usefulness of galantamine, donepezil, and memantine (Veronese et al, 2016). …”
Section: Efficacy Datamentioning
confidence: 99%
“…In line with results for unipolar depression (Reynolds 2011), a recent review in mainly working-age adults shows that acetylcholinesterase inhibitors (AChEIs) are not helpful in reducing mood or psychotic symptoms in bipolar depression and mania (Veronese 2016). However, the review reports on only three randomised controlled trials (RCTs) of AChEIs.…”
Section: Acetylcholinesterase Inhibitors and Memantinementioning
confidence: 94%